Presupuesto, gasto público y compra pública responsable en Ecuador (Tema Central) - Guerra Zúñiga, Eddy María de la (2016)
The General Budget of the State that was traditionally legislated in Ecuador through a law before 2008, today is just a “tool” whose legal nature is complex to determinate, and it is used for planning of income and expenditure. Such determination should be based, at least in theory, a technical study and the result of an intelligent planning, designed to satisfy the most possible public needs with the available resources. In that sense, public procurement has a double connotation: permanent governance mechanism which the effect of generate a budgetary expenditure; and a tool for achieving the aims of fiscal policy of the State. Under any view, public procurement should be not only sustainable but also responsible. The responsibility standards are guiding the development of this paper.